Laboratory Safety Awareness Among General Physics Undergraduate Students - Ponferrada, C. O.; Daque, J. G.; Buadlart, D. C. L.; Cabigon, E. J. L.; Galarpe, V. R. K. R. (Engineering, Technology & Applied Science Research, 2017)
Safety awareness in the laboratory is essential to reduce occupational risks. This study was conducted to determine the students’ safety awareness in a Physics laboratory. This study determined the student perception towards safety awareness by factors of gender and college from which students are enrolled. A sum of 324 students enrolled in Physics10 (Mechanics and Heat) and Physics11 (Electricity and Magnetism) in the Mindanao University of Science and Technology (MUST) were randomly selected as survey respondents. A modified survey questionnaire was used as research instrument. The results show that the students had positive level of safety awareness and perceived positively on the preventive measures to reduce laboratory risk. Further, regardless of gender students enrolled in Physics 10 were more positively aware towards safety awareness than students enrolled in Physics 11. Similarly, a variation among the students perception towards safety awareness from the College of Engineering and Architecture (CEA) and College of Industrial and Information Technology (CIIT) occurred. Overall, present findings indicate a need to introduce laboratory safety awareness in Physics classes.